Positioning Asian Australian writing in anthologies of Australian literature and Australian literary history - Ramlan, Wan Nur Madiha; Abdul Kadir, Maimunah (2020)
This article examines the politics within the processes of canonising national literatures. In particular, it is a study of a number of anthologies of Australian literature to analyse what they might tell us about how Asian Australian writing in is posited within a national literary canon and history. Interestingly, despite the growing focus on Asian Australian writing in recent years, how these literary texts are anthologised as part of Australian literary tradition has not attracted the same amount of attention. Major anthologies focused on national literatures can measure how texts are regarded as important and merit the need for conservation. Anthologies are therefore a genre in which a literary canon emerges and can be examined. They also expose the mechanics of a particular theme, perception, or ideology about the status of literature as a reflection of a nation’s socio-cultural and historical landscape. Hence, this study charts the trends behind the inclusion or exclusion of Asian Australian writing within the national literary narrative by analysing four different anthologies of Australian writing. These anthologies are The Oxford Anthology of Australian Literature (1985), The Macmillan Anthology of Australian Literature (1990), Australian Literature: An Anthology of Writing from the Land Down Under (1993) and Macquarie PEN The Literature of Australia (2010). It also makes reference to two anthologies dedicated to Asian Australian writing, particularly Growing Up Asian in Australia (2008) and Contemporary Asian Australian Poets (2013) in order to further look at the state of Asian Australian writing and how they help increase the visibility of Asian Australian writers.